Penerapan Sanksi Pidana Terhadap Korporasi Dalam Berbagai Putusan Pengadilan - Surbakti, Feri Antoni; Azheri, Busyra (Faculty of Law, Andalas University, 2024)
The existence of corporations as legal subjects that can be held criminally accountable has long been regulated in various laws outside the Criminal Code (KUHP), especially in administrative penal law. The issuance of Supreme Court Regulation (PERMA) No. 13 of 2016 concerning Procedures for Handling Criminal Cases by Corporations, as is known, was motivated by the numerous laws that have positioned corporations as legal subjects of criminal law and that can be held criminally accountable. This writing addresses two issues: the implementation of handling criminal cases with corporations as legal subjects in various court decisions, and the obstacles in executing criminal sanctions against corporations. The method used in this writing is normative juridical research, employing a conceptual approach, a statutory approach, a historical approach, and a case approach. The nature of this research is descriptive, and the data used is secondary data collected through literature and document studies. The data analysis in this writing will be conducted qualitatively. The results and discussion in this writing show that the handling of criminal cases involving corporations has increasingly been addressed by law enforcement officials. This growing number of corporate cases, of course, is inseparable from the issuance by the Supreme Court of regulations on procedures for handling criminal cases involving corporations as legal subjects. The handling of criminal cases with corporations as legal subjects already covers both corporations with legal entity status and those without (non-legal entities). The handling of criminal cases with corporations as defendants that have been decided by courts and have obtained legal force in execution encounters challenges. These obstacles and difficulties reduce the effectiveness of criminal law enforcement. Court decisions in adjudicating criminal cases with corporations as perpetrators (defendants) should not only apply the law textually but also ensure that these decisions can be effectively executed.